The effect of simvastatin on thromboxane-mediated contraction in porcine coronary artery: investigation of the role of mitochondria and extracellular calcium - Saarti, Mohammed (2019)
Cardiovascular diseases (CVDs) have a severe impact on human health, increasing the risk of morbidity and mortality. Atherosclerosis is one of the common caused of CVD because the plaques formed cause the affected arteries to narrow, leading to diminished blood flow, ischaemia and hence damage to organs. Statins (3-hydroxymethyl-3-methylglutaryl coenzyme A [HMG-CoA] reductase inhibitors) are one of the most well-known, effective and safe groups of drugs used for treating and preventing the recurrence of this condition. They decrease the incidence of disease (morbidity) and the rate of death (mortality). All statins act by inhibiting the conversion of HMG-CoA to mevalonic acid, which is responsible for the synthesis of cholesterol and consequently associated with a reduction in serum total and low-density lipoprotein (LDL) cholesterol. Statins are effective medications for the primary and secondary prevention of coronary heart disease (CHD). The overall beneficial effects of statins not only come from the reduction of cholesterol, but also come from cholesterol-independent effects known as pleiotropic effects. Previous studies in the laboratory have indicated the statins, such as simvastatin, cause relaxation of blood vessels through inhibition of mitochondrial complexes. The data also indicated that simvastatin might act to reduce calcium influx through voltage gated calcium channels. However, it is not clear whether the effects on the mitochondria are related to the inhibition of calcium influx. Studies revealed that mitochondria are able to regulate intracellular calcium levels, and, therefore, influx through calcium channels. Furthermore, statins have also been reported to inhibit Rho kinase and ERK, both of which can regulate vascular tone. Although this has been linked to inhibition of isoprenylation, whether this is also related to the effects on the mitochondria is unknown. Therefore, the aim of this study was to determine the effect of simvastatin on U46619-induced contraction in porcine coronary artery (PCA) and to determine whether inhibition of mitochondrial function could underlie effects on calcium, Rho kinase and ERK. Comparisons were made with known mitochondrial complex inhibitors in order to understand how inhibition of mitochondrial complexes could regulate vascular tone. The study showed that simvastatin inhibits the U46619-induced contraction in PCA only in the presence of calcium possibly via mitochondrial inhibition. The combination of inhibitors of mitochondrial complexes I and III (rotenone-myxothiazol) reduced this inhibitory effect while the combination of mitochondrial inhibitors rotenone-antimycin A enhanced the inhibitory effect of simvastatin. The combination of rotenone-myxothiazol prevented the inhibitory effect of simvastatin on the BAY K8644-induced contraction (L-type Ca2+ channel activator) suggesting that the effects of simvastatin on calcium-induced contractions may be due to mitochondrial effects. The effect of mitochondrial complex III inhibitors, antimycin A and myxothiazol, were examined as a comparison with simvastatin. Antimycin A inhibits the contractile responses in PCA and this effect was mediated through inhibition of calcium influx through L-type calcium channels as well as via a calcium-independent pathway. Unlike simvastatin, the combination of rotenone-myxothiazol had no effect on the antimycin A inhibitory effect, suggesting differences between the mechanism of action of simvastatin and antimycin A. On the other hand, both simvastatin and myxothiazol inhibited the contractile responses in PCA only in the presence of calcium and the data suggest that the anti-contractile effects of both are mediated through inhibition of calcium influx through L-type calcium channels. The study showed that simvastatin, myxothiazol, and antimycin A inhibited CaCl2-induced contraction and BAY K 4668-induced contraction. In addition, the nifedipine-induced relaxation was partially inhibited at the higher concentrations by simvastatin and myxothiazol but not antimycin A. These data suggest that inhibition of complex III at the Qo site, the site that can be blocked with myxothiazol, leads to inhibition of calcium influx through L-type calcium channels. Finally, experiments on isolated mitochondria showed that simvastatin had no direct effect on the mitochondria, in contrast to previous studies in intact tissues and cells. Antimycin A and myxothiazol (complex III inhibitors) both changed the Rh123 fluorescence, indicating that they decreased the mitochondrial membrane potential. As a conclusion, the data from the functional studies support the hypothesis that simvastatin produces anti-contractile effects through inhibition of the Qo site at mitochondrial complex III. The data also support the hypothesis that inhibition of complex III at the Qo site leads to inhibition of calcium influx through L-type calcium channels, although how this occurs is yet unknown.